Stimulation Of Local Cultural Values And Wisdom In The Globalization Era - Harianto II; Zulfitri Zulfitri; Teguh Satria Amin (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
Globalization is one of the changes in the pattern of life in a group of individuals or a society that has headed towards modernization. This era of globalization will certainly result in people who tend to choose new cultures that are fresher and simpler, causing local culture to begin to erode and be forgotten and even a shift in values from the local culture. This is one of the factors that causes local culture to be abandoned and also forgotten nowadays. The absence or reduction of the younger generation who are successors and inheritors of local culture and wisdom has made interest in learning and getting to know one's own culture begin to fade. Today's young generation has neither the effort nor the interest to preserve local culture or local culture which is Indonesia's wealth in this era of globalization. The research method used is a qualitative method with literature study techniques in data collection. Based on the narrative from Malinowski, cultures that are in a higher caste and are active will have a great influence on cultures that are lower and tend to be passive. And this influence can occur in cultural contact. This theory is clearly visible in the current era of globalization. This can be seen from the shift in Indonesian cultural values which have begun to lean towards the west with the rapid flow of incoming information. This is of course a force that can influence people's thinking. In order to overcome this, it certainly requires awareness of the importance of local culture as identity and also national identity. It is the obligation of every society to preserve and also maintain culture with the help of the younger generation as heirs to that culture.